DEVELOPMENT OF LEARNING EVALUATION TEST ON WORK AND ENERGY MATERIALS FOR GRADE VIII SMP - Fauziyah, Emy; Lina Arifah Fitriyah (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2024)
Learning evaluation is process to get information to know learning acceptable or not to students. This research aims to develop evaluation questions form multiple choices on work and energy material theoretically and empirically for grade VIII  SMP. Development model used ADDIE, consists of  stages : Analyze, Design, Development, Implementation, Evaliation. Theoretical validity test obtained from assesment evaluation test from material experts, media experts and practitioners from science teachers. Empirical validity testing obtained from analyzing data from results of  testing evaluation test on students includes validity, reliability, level of difficulty, differentiability of questions. Results from  validator got  score 99,3 % and in very good criteria. Question validity test results  65% the questions valid and 35% the questions invalid. Question reliability test results a calculated r value of 0.774 and in high category. Difficulty level test results of the questions were 20%, 40%, 40% with categories difficult, medium and easy. Different power test results of the questions each received a score of 25% with the criteria very good, good, fair and low.  Thus, the evaluation test of work and energy material are worthy of being tested on class VIII students.